Meningkatkan Minat dan Kemampuan Membaca Siswa Pada Kelas 1 dan 2 UPT SDN.060837 Medan Barat - Riska Azizah; Randa Putra Kasea Sinaga; Masnita Masnita (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Teaching Campus is a learning channel that provides opportunities for students to study off-campus for one semester in order to practice their ability to solve complex problems by becoming partners with teachers to innovate in learning, develop strategies and learning models that are creative, innovative and fun. Through this program, students will be more active in the field and hone creativity for sustainability and improving the quality of education. For this reason, this journal will explain how this teaching campus program is carried out. Placements in campus teaching programs certainly vary. This journal will explain the USU Partners teaching campus program which is carried out at UPT SD 060837 which is located at Jalan Sei Deli number 3, Silalas Village, West Medan District. At this elementary school, the focus of the program is aimed at literacy, namely learning to read for grades 1 and 2 at the elementary school. The USU Partner Teaching Campus Program lasts for 4 months, starting from March to June 2023. With an approach using methods in social work, namely case work and group work in carrying out the program.